The Role of Depression, Anxiety And Stress Against Hypertension In The Elderly - Noviana Dewi; Faqih Purnomosidi (Psycho Idea, 2019)
The purpose of this research is to determine the correlation of depression, anxiety and stress to blood pressure in the elderly. Hypertension has been treated with drug therapy and control of food intake so far, but there are not many treatments related to psychological factors that can cause hypertension. Psychological factors have a role in influencing the emergence of physical illness. This research uses a quantitative correlation method design with data collection using DASS Test to measure the level of depression, anxiety, and stress with validity of 0.266-0.769 and reliability of 0.939 while blood pressure measurements were measured using sphygmomanometer. The research results showed that there was a very strong correlation between depression, anxiety and stress on blood pressure in the elderly with a correlation of 0.875 which means that the higher the level of depression, anxiety, and stress in the elderly, the higher the tendency of hypertension.